(untitled) (The Agriculturists, 2018)
An experiment was conducted at the experimental farm of the Department of Genetics and Plant Breeding, Bangladesh Agricultural University, Mymensingh with fifteen maize (Zea mays L.) genotypes to assess the genetic variability, characters association and divergence among the genotypes for yield and yield attributing traits. The experiment was conducted during November 2015 to May 2016, following Randomized Complete Block Design (RCBD) with three replicates in two adjacent environments to discern the performance of the genotypes in interacting environments. No significant variation was observed for environments, which was perhaps due to their close proximity. The genotypes differed significantly for most of the studied traits. The phenotypic co-efficient of variation (PCV) was higher than genotypic co-efficient of variation (GCV) for all the evaluated traits. High heritability along with high genetic advance was observed for 1000 seed weight, seed numbers ear-1 and yield plant-1. Yield plant-1 was significantly associated with plant height, ear length, ear girth, husk girth, kernel length, 1000 seed weight, kernel numbers row-1, seed numbers ear-1 in positive direction and negatively associated with days to anthesis and moisture loss (%). Path co-efficient analysis revealed that the maximum positive direct contribution towards yield was through 1000 seed weight, seed number ear-1 and kernel length whereas plant height, ear girth, ear length, kernel numbers row-1 showed negative direct contribution towards yield due to negative indirect effects of several parameters. Cluster analysis exhibited five distinct groups. Considering mean values Cluster II provided the best result in terms of yield and earliness, followed by Cluster IV and V. The results of principal component analysis (PCA) revealed that first five components accounted for 82.7% of total variation. The findings indicate the presence of ample genetic diversity among maize genotypes which can be exploited in future breeding program for better utilization of maize germplasm. The Agriculturists 2017; 15(2) 101-114